Recent Changes in the ISBA‐CTRIP Land Surface System for Use in the CNRM‐CM6 Climate Model and in Global Off‐Line Hydrological Applications. (3rd May 2019) - Decharme, Bertrand; Delire, Christine; Minvielle, Marie; Colin, Jeanne; Vergnes, Jean‐Pierre; Alias, Antoinette; Saint‐Martin, David; Séférian, Roland; Sénési, Stéphane; Voldoire, Aurore
Abstract: In recent years, significant efforts have been made to upgrade physical processes in the ISBA‐CTRIP land surface system for use in fully coupled climate studies using the new CNRM‐CM6 climate model or in stand‐alone mode for global hydrological applications. Here we provide a thorough description of the new and improved processes implemented between the CMIP5 and CMIP6 versions of the model and evaluate the hydrology and thermal behavior of the model at the global scale. The soil scheme explicitly solves the one‐dimensional Fourier and Darcy laws throughout the soil, accounting for the dependency of hydraulic and thermal soil properties on soil organic carbon content. The snowpack is represented using a multilayer detailed internal‐process snow scheme. A two‐way dynamic flood scheme is added in which floodplains interact with the soil hydrology through reinfiltration of floodwater and with the overlying atmosphere through surface free‐water evaporation. Finally, groundwater processes are represented via a two‐dimensional diffusive unconfined aquifer scheme allowing upward capillarity rises into the superficial soil. This new system has been evaluated in off‐line mode using two different atmospheric forcings and against a large set of satellite estimates and in situ observations. While this study is not without weaknesses, its results show a real advance in modeling the physical aspects of the land surface with the new ISBA‐CTRIP version compared to the previous system. This increases our confidence that the model is able to represent the land surface physical processes accurately across the globe and in turn contribute to several important scientific and societal issues. Key Points: Land Surface Modeling for global climate and hydrological applications soil, snow, river, groundwater and floodwater processes